Seventy Five Cases Of Exfoliative Dermatitis - Bandyaopadhyay Debabrata; Chowdhury Satyendra Nath; Roy Aloke Kr (Wolters Kluwer Medknow Publications, 1999)
A study of 75 cases of exfoliative dermatitis showed a male preponderance (M:F=4.77:1) with highest frequency of occurrence in the fifth and sixth decades. Cutaneous ailments were responsible for 64% of cases, among which psoriasis was the commonest disease followed by various types of eczema. The syndrome was caused by drugs in 12% of the cases and malignancy in 2.67%. In 21.33% of patients the cause remained undetermined. The systemic changes and the laboratory findings are described.